The Optimal Consumption of Depletable Natural Resources: Comment - Kemp, Murray C.; Long, Ngo Van (Quarterly Journal of Economics, 1978)
Monopoly, 346.—Competition, 347.—Comparison of the monopolistic and competitive paths, 349.—The socially optimal path, 351.—Final remarks, 351.